Records Management Implementation In Finance Unit, Pustaka Negeri Sarawak / Amal Amilla Sahat - Sahat, Amal Amilla (University Technology MARA Sarawak, 2014)
Sarawak State Library or its equivalent in Bahasa Malaysia, Pustaka Negeri Sarawak was launched on 31st December 1999, officiated by Yang Amat Berhormat Pehin Sri Abdul Taib Mahmud, former Sarawak Chief Minister and open to public on 2nd January 2000. The establishment of Pustaka Negeri Sarawak stipulated under the Laws of Sarawak, Chapter 29, Sarawak State Library Ordinance 1999 (Sarawak State Library Ordinance, 1999). Pustaka Negeri Sarawak serves as a community centre of knowledge and cultural enlightenment where Malaysians in Sarawak not only access a vast store of information also as the hub of information services in the form of both printed and electronic media for the public and private sectors elsewhere in Sarawak throughout Malaysia. It will also provide gateway into from publicly accessible international information centers. This will help the state to grow into an information, communication and technology and in line with country's vision of 2020.